Modeling of Congo Red Adsorption onto Multi-walled Carbon Nanotubes Using Response Surface Methodology: Kinetic, Isotherm and Thermodynamic Studies - Selen, Veyis; Guler, Omer (Springer Heidelberg, 2021)
In this present study, an adsorption process was investigated to removal of Congo Red (CR) dye from aqueous solutions by using multi-walled carbon nanotubes (MWCNTs) as an adsorbent. The physico-chemical properties of MWCNTs were characterized by TEM, SEM, Raman spectroscopy and BET surface area. The response surface methodology, which is including central composite design, was used to investigate the effects of four independent parameters (initial pH of solution (5.5-11.5), initial CR concentration (15-75 mg/L), MWCNTs amount (0.05-0.25 g/L) and contact time (20-60 min)). ANOVA evaluated with Design Expert 10.0 showed that a high value of regression coefficient (R-2 = 0.988) a good agreement between experimental and model predicted response in addition to significance of the model. The optimum values of the independent variables giving the maximum removal efficiency (78.36%) of CR dye were obtained at the optimum adsorption conditions of initial solution pH: 5.5; initial CR concentration: 15 mg/L; MWCNTs dosage: 0.25 g/L and contact time: 59.62 min. The kinetic study illustrated that the experimental data are well defined with pseudo-second-order adsorption kinetic model. The maximum adsorption capacity (q(max)) increased from 115.8 mg/g to 138.3 mg/g with the increase in temperature from 293 to 323 K. Thermodynamic parameters, Delta H (8.56 kJ/mol), Delta G (- 27.08 and - 30.73 kJ/mol) and Delta S (0.1215 kJ/mol K) were determined for the adsorption process.
Keywords: Adsorption; Congo red; MWCNTs; Response surface methodology; Thermodynamics